Locomotor and gait changes in the LPS model of neuroinflammation are correlated with inflammatory cytokines in blood and brain - Diogo Carregosa; Natasa Loncarevic-Vasiljkovic; Raquel Feliciano; Diogo Moura-Louro; César S. Mendes; Cláudia Nunes dos Santos (BMC, 2024)
Abstract Lipopolysaccharide (LPS) challenge in mice has been used to identify the mechanisms and therapeutics for neuroinflammation. In this study, we aimed to comprehensively evaluate the behavioral changes including locomotion, exploration, and memory, correlating them with a panel of thirteen inflammatory cytokines in both blood and brain. We found that acute LPS administration (0.83 mg/Kg i.p.) reduced body weight, food intake, and glucose levels compared to the saline-injected mice, concomitant with decreased activity in home cage monitoring. Locomotion was significantly reduced in Open Field, Introduced Object, and Y-Maze tests. Decreased exploratory behavior in the Y-Maze and Introduced Object tests was noticed, by measuring the number of arms explored and object interaction time, respectively. Additionally, in rotarod, LPS administration led to a significant decrease in the distance achieved, while in the MouseWalker, LPS led to a reduction in average velocity. LPS induced a decrease in microglia ramification index in the motor cortex and the striatum, while surprisingly a reduction in microglia number was observed in the motor cortex. The concentrations of thirteen cytokines in the blood were significantly altered, while only CXCL1, CCL22, CCL17, G-CSF, and IL-12p40 were changed in the brain. Correlations between cytokine levels in blood and brain were found, most notably for CCL17 and CCL22. TGFβ was the only one with negative correlations to other cytokines. Correlations between cytokines and behavior changes were also disclosed, especially for CCL17, CCL22, G-CSF, and IL-6 and negatively for TGFβ and IL-10. In summary, our study employing acute LPS challenge in mice has revealed a comprehensive profile of behavioral alterations alongside significant changes in inflammatory cytokine levels, both in peripheral blood and brain tissue. These findings contribute to a deeper understanding of the interplay between inflammation and behavior, with possible implications for identifying prognostics and therapeutic targets for neuroinflammatory conditions.